Atlantic salmon show capability for cardiac acclimation to warm temperatures - Anttila, Katja; Couturier, Christine S.; Øverli, Øyvind; Johnsen, Arild; Marthinsen, Gunnhild; Nilsson, Göran E.; Farrell, Anthony P. (Nature communications, 2014)
Increases in environmental temperature predicted to result from global warming have direct effects on performance of ectotherms. Moreover, cardiac function has been observed to limit the tolerance to high temperatures. Here we show that two wild populations of Atlantic salmon originating from northern and southern extremes of its European distribution have strikingly similar cardiac responses to acute warming when acclimated to common temperatures, despite different local environments. Although cardiac collapse starts at 21–23 °C with a maximum heart rate of ~\n150 beats per min (bpm) for 12 °C-acclimated fish, acclimation to 20 °C considerably raises this temperature (27.5 °C) and maximum heart rate (~\n200 bpm). Only minor population differences exist and these are consistent with the warmer habitat of the southern population. We demonstrate that the considerable cardiac plasticity discovered for Atlantic salmon is largely independent of natural habitat, and we propose that observed cardiac plasticity may aid salmon to cope with global warming. Cardiac function can limit high-temperature tolerance in fish. Here, Antilla et al. show similar cardiac responses to warming for two wild Atlantic salmon populations with different environmental temperatures, which suggests that cardiac plasticity is independent of natural habitat.